(untitled) (Research, Society and Development, 2021)
Objective: To characterize patients suffering from rheumatic disease in a specialty center in the interior of the Amazon. Methodology: Retrospective, observational, cross-sectional study with a quantitative approach of a sample of 182 medical records of individuals being monitored at the rheumatology service in the period between December 31, 2019 and January 1, 2020 in a specialty center located in the city of Maraba, Para, Brazil. Results: It was observed that there was a predominance of female patients (92.31%), aged between 61 and 70 years (37.36%). The main diagnosis found was fibromyalgia followed by rheumatoid arthritis. The main comorbidities found were SAH and DM and the main drug used was pregabalin, in agreement with the main diagnosis. Contrary to numerous studies on the profile of rheumatologic patients, all patients had a treatment time of less than 5 years. Conclusion: Through the results, it can be seen that the municipality of Marabá follows national statistics in the scope of the epidemiology of rheumatologic diseases. Thus, the understanding of this profile can provide medium and long-term improvements in the monitoring of patients in the field of rheumatology, enabling comprehensive care.